2019
DOI: 10.1038/s41598-019-40275-5
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and neurophysiological impacts of plant essential oil components on bed bugs (Cimicidae: Hemiptera)

Abstract: Bed bugs ( Cimex lectularius L.) are globally important human parasites. Integrated pest management (IPM) approaches, which include the use of essential oil-based insecticidal compounds, have been proposed for their control. This study aimed to define insecticidal activity and neurophysiological impacts of plant essential oil constituents. The topical and fumigant toxicity of 15 compounds was evaluated against adult male bed bugs. Neurological effects of the 6 most toxicologically active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 63 publications
2
78
0
Order By: Relevance
“…In contrast, eugenol was the most toxic compound in the contact bioassay. The fumigant toxicity of some essential oils' components was evaluated against bed bugs (Cimex lectularius L.) and it was found that cyclic monoterpenoids thymol and carvacrol had much more fumigant toxicity than bicyclic monoterpenoids camphor and 1,8-cineole, cyclic monoterpene limonene, bicyclic monoterpene α-pinene, and phenylpropanes cinnamaldehdye, citronellic acid, eugenol and methyl eugenol [93]. Consequently, although the high insecticidal effects of monoterpenes, monoterpenoids, sesquiterpenes, sesquiterpenoids, and phenylpropanes has been reported, on the one hand, the monoterpenoids, especially cyclic monoterpenoids, showed the most toxic effects.…”
Section: Chemical Composition Of Essential Oils and Their Relative Pementioning
confidence: 99%
“…In contrast, eugenol was the most toxic compound in the contact bioassay. The fumigant toxicity of some essential oils' components was evaluated against bed bugs (Cimex lectularius L.) and it was found that cyclic monoterpenoids thymol and carvacrol had much more fumigant toxicity than bicyclic monoterpenoids camphor and 1,8-cineole, cyclic monoterpene limonene, bicyclic monoterpene α-pinene, and phenylpropanes cinnamaldehdye, citronellic acid, eugenol and methyl eugenol [93]. Consequently, although the high insecticidal effects of monoterpenes, monoterpenoids, sesquiterpenes, sesquiterpenoids, and phenylpropanes has been reported, on the one hand, the monoterpenoids, especially cyclic monoterpenoids, showed the most toxic effects.…”
Section: Chemical Composition Of Essential Oils and Their Relative Pementioning
confidence: 99%
“…[11]. Of the various monoterpenoids tested in a recent study, the phenolic compounds carvacrol, eugenol and thymol were found to possess potent insecticidal activity against insecticide susceptible bed bugs when applied topically and/or as fumigants [20]. Furthermore, electrophysiology studies showed that these compounds also cause neuroinhibitory effects, i.e., suppression of the nervous system or nerve firing activity [20].…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate that carvacrol acted earlier, before the integrity of the midgut cells was disturbed or affected in other insect tissues than the haemolymph. In topical and fumigant bioassays performed by Gaire et al (2019), carvacrol demonstrated neuro-inhibitory effects in hemipteran insect. Rizvi et al (2018) showed that carvacrol inhibited acetylcholinesterase activity in insects of the same order by contact application.…”
Section: Discussionmentioning
confidence: 99%
“…Carvacrol or plant extracts with carvacrol as the main component are known to exert negative effects against coleopteran (Szczepanik et al 2018), homopteran (Zekri et al 2016), dipteran (Andrade-Ochoa et al 2018;de Mesquita et al 2018;Giatropoulos et al 2018), lepidopteran (Melo et al 2018), neuropteran (Castilhos et al 2018), and hemipteran (Gaire et al 2019;Rizvi et al 2018) insects. This phytochemical was shown to exhibit contact (Castilhos et al 2018;Melo et al 2018;Rizvi et al 2018), repellent (Giatropoulos et al 2018), and fumigant (Gaire et al 2019) toxicity. The carvacrol-containing essential oil showed neurotoxic effects and was found to inhibit the acetylcholinesterase enzyme in the contact application against insect pests (de Mesquita et al 2018;Rizvi et al 2018).…”
Section: Introductionmentioning
confidence: 99%